Prognostic value of proadrenomedullin in patients with COVID-19 pneumonia - Astapovskii, Aleksandr A.; Drozdov, Vladimir N.; Shikh, Evgenia V.; Melkonyan, George G.; Sizova, Zhanna M.; Zakharova, Valeria L.; Shindryaeva, Natalia N.; Lapidus, Natalia I. (Frontiers in Medicine, 2022)
Objective The aim of the study was to assess the role of mid-regional proadrenomedullin (MR-proADM) in comparison with routine laboratory tests in patients with COVID-19. Materials and methods 140 hospitalized patients aged 18 and older with COVID-19 pneumonia were included in prospective single-center study. Routine analyses were performed, and MR-proADM level was measured within the first and the third hospital days using Human MR pro-ADM (Mid-regional pro-adrenomedullin) ELISA Kit with a sensitivity of 0.469 pmol/L (immunofluorescence assay). National Early Warning Score (NEWS) was used for primary assessment of the disease severity. According to disease outcome the patients were divided into two groups: discharged patients (n = 110, 78.6%) and deceased patients (n = 30, 21.4%). Results: The groups had no statistically significant difference in sex, comorbidity, body temperature, oxygen saturation level, heart rate, respiratory rate, and C-reactive protein (CRP) level and procalcitonin (PCT). The deceased patients had statistically significant difference in age (median, 76 years; interquartile range, 73.2–78.2 vs. median, 66 years; interquartile range, 62–67; p < 0.0001), NEWS value (median, 5; interquartile range, 3–8 vs. median, 2; interquartile range, 0–6; p <0.05), hospitalization period (median, 17; interquartile range, 7–35 vs. median, 6; interquartile range, 3–14), quantitative CT extent of lung damage > 50% [n = 26 (86.7%) vs. n = 9 (8.2%) p < 0.0001], level of leukocytes (median, 11.4 ×109/L; interquartile range, 6.2–15.5 vs. median, 5.3 ×109/L; interquartile range, 4.7–6.4; p = 0.003), level of neutrophils (median, 80.9%; interquartile range, 73.6–88.6 vs. median, 72.6%; interquartile range, 68.7–76.9; p = 0.027), level of MR-proADM at the first hospital day (median, 828.6 pmol/L; interquartile range, 586.4–1,184.6 vs. median, 492.6 pmol/L; interquartile range, 352.9–712.2; p = 0.02), and level of MR-proADM at the third hospital day (median, 1,855.2 pmol/L; interquartile range, 1,078.4–2,596.5 vs. median, 270.7 pmol/L; interquartile range, 155.06–427.1). Conclusion Mid-regional proadrenomedullin has a higher prognostic value in patients with COVID-19 in comparison with routine inflammatory markers (leukocyte and neutrophils levels, CRP, and PCT) and NEWS.